Системи контролю початкового розвитку сучасних селекційних зразків озимих зернових колосових культур у СГІ – НЦНС - Стельмах, А.Ф.; Файт, В.І. (Фактори експериментальної еволюції організмів, 2015)
Aims. To evaluate breeding lines and cultivars on their vernalization requirement duration and photosensitivity level.
Methods. Heading date registration after various duration of artifi cial vernalization and planting in long and short
daylength. Results. The majority of modern winter bread wheat lines showed lowered vernalization requirement and
weak photosensitivity, possibly relating to higher yield. And only solitary stocks revealed stronger reactions, although
they relate to frost resistance improvement. The lines of alternative barley revealed very strong photoreactions which
compensate their losses in autumn initial development delay due to almost full absence of vernalization requirement. The
last characteristic was expressed (even pronounced — more than 40 days) in typical winter stocks, what allows to expect
suffi cient frost resistance when it is followed by strong photosensitivity, although the last was revealed in rare winter lines
yet. Conclusions. Leading breeders of cereals are again interested in evaluation of physiological systems infl uencing
initial development as having adaptive value.
Keywords: winter wheat and barley, modern breeding lines, vernalization requirement duration, level of photosensitivity.